STOCK PRICE DYNAMICS IN TECHNOLOGY COMPANIES : THE ROLE OF PROFITABILITY, LEVERAGE AND FIRM SIZE - Teguh Firmansyah (LPPM STIE Muhammadiah Bandung, 2026)
This research investigates the impact of profitability, financial leverage, and firm size on the stock prices of technology firms listed on the Indonesia Stock Exchange from 2021 to 2024. A quantitative research design is applied using secondary data derived from companies’ annual financial reports and stock price records. The study examines 29 technology companies, yielding 116 firm-year observations selected through purposive sampling. Descriptive statistical analysis and multiple linear regression are employed to analyze the data. The findings reveal that firm size exerts a positive and significant influence on stock prices, whereas profitability and financial leverage show no significant effect. Collectively, the independent variables explain only a limited proportion of stock price fluctuations. These results suggest that stock price movements in the technology sector are driven more by company scale than by short-term financial performance indicators. This study offers valuable implications for investors, corporate management, and academics in assessing stock price dynamics within Indonesia’s technology industry.